EXPLORATION OF QUANTUM MECHANICS IN EVERYDAY PHENOMENA - Gurikar, Shivaraj G (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Quantum mechanics, the branch of physics that deals with the behavior of matter and energy at atomic and subatomic scales, may seem like a highly theoretical subject confined to laboratories, but its principles are deeply embedded in our everyday lives. This study explores the profound influence of quantum mechanics on various phenomena and technologies that shape modern society. Concepts such as wave-particle duality, superposition, and quantum entanglement, though initially counterintuitive, provide explanations for numerous occurrences and innovations in our daily existence. One of the most visible impacts of quantum mechanics is in the realm of technology. Semiconductors, integral to devices like smartphones, computers, and televisions, operate on principles of quantum mechanics, enabling the development of advanced electronics. Additionally, quantum phenomena underpin technologies such as lasers, LEDs, and MRI machines, revolutionizing fields from medicine to communication. Quantum mechanics also plays a crucial role in natural processes, such as photosynthesis, where quantum coherence boosts energy efficiency in plants. In the biological realm, quantum effects influence senses like smell and vision, adding another layer to the complexity of life. Even the colors we see in objects or the efficiency of solar panels are outcomes of quantum principles at work. Beyond practical technologies, quantum mechanics challenges our fundamental understanding of the universe. Concepts like the uncertainty principle and quantum superposition disrupt classical views of reality, leading to new perspectives on causality and measurement. As quantum research progresses, its applications are poised to expand further, potentially leading to breakthroughs in fields like quantum computing, cryptography, and energy systems. This exploration emphasizes how quantum mechanics, despite its abstract nature, is central to both the technologies and the natural phenomena that define our everyday experiences.